(untitled) (International Journal of Criminology and Sociology, 2021)
This paper uses Hartzell and Hoddie’s four dimensions of power-sharing to analyse the implementation of the 2008 power-sharing in Zimbabwe and its impact on electoral violence. It interrogates the resolving of the Zimbabwean electoral violence through the use of power-sharing deal between the opposition and the ruling party. The theoretical explanations why electoral violence would occur in a country ruled by an authoritarian leadership suggests that, autocratic governments use electoral violence as a way of influencing the electoral outcome. The other position suggests that the weaker political party is the one responsible for electoral violence as it enjoys the monopoly of being the victim. This study dispels the notion that power-sharing has any impact on resolving electoral violence permanently, we argue that the resolving election dispute through power-sharing does not resolve the differences between warring parties rather, it gives temporary peace. The findings of this study support the position of the electoral authoritarian theoretical perspective that autocratic government will use violence and all the means necessary to ensure that they return the power.